First Record of Bradoponera wunderlichi (Hymenoptera, Formicidae) from Rovno Amber, with Description of the Worker Caste - A. G. Radchenko; M. R. Khomych; M. M. Kalmer (Zoodiversity, 2025)
Previously unknown workers of Bradoponera wunderlichi Baroni Urbani & De Andrade, 2003 are described, and this extinct species is recorded for the first time in Rovno amber. We show that the lectotype of Bradoponera meieri Mayr, 1868 was previously designated by Dlussky (2009) based on a wrong collection number, which is corrected here.